2011
DOI: 10.4103/0975-7406.90106
|View full text |Cite
|
Sign up to set email alerts
|

Resistant patterns of bacteria isolated from bloodstream infections at a university hospital in Delhi

Abstract: Background:The choice of antimicrobial therapy for bloodstream infections is often empirical and based on the knowledge of local antimicrobial activity profiles of the most common bacteria causing such infections.Aims:The present study was aimed to investigate frequency of bacterial pathogens causing septicemia and their antimicrobial resistant pattern in hospital admitted patients.Settings and Design:It was a prospective study, conducted at Majeedia Hospital, Hamdard University, New Delhi, India.Material and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
28
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 13 publications
11
28
2
Order By: Relevance
“…Commonest gram negative bacteria isolated in our study was E.coli , Klebsiella spp and followed by Salmonella spp and non-fermenters (Pseudomonas and Acinetobacter spp) which was in concordance with other studies carried out in different parts of India [14,15] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Commonest gram negative bacteria isolated in our study was E.coli , Klebsiella spp and followed by Salmonella spp and non-fermenters (Pseudomonas and Acinetobacter spp) which was in concordance with other studies carried out in different parts of India [14,15] .…”
Section: Discussionsupporting
confidence: 93%
“…The gram positive organism especially Staphylococcus aureus showed 41.4% and 55.24% sensitivity to penicillin and erythromycin respectively but were 100 sensitive to Vancomycin and Linezolid similar sensitivity pattern were seen in other studies [11,14,15] . 41(22.65%) were detected as methicillin resistant Staphylococcus aureus (MRSA).…”
Section: Discussionsupporting
confidence: 81%
“…For example, our study also reports that bacteremia is significantly more frequent in males than in females which is consistent with another study (6). Like other studies from Iran, the most common type of cancer in our study was gastric cancer (12,13).…”
Section: Discussionsupporting
confidence: 93%
“…Many investigations have reported that among blood born infections, gram-negative bacteria are associated with more mortality than gram-positive bacteria (3,4). On the other hand, many scientists also report that the causative agents of bacteremia are changing (5,6); therefore, obtaining a better understanding of the spectrum of pathogens causing bacteremia is vital for prompt treatment.…”
Section: Introductionmentioning
confidence: 99%
“…2 In our study, blood culture positivity was 17.18% which is comparable to study by Gulrez In our study, the isolation rate of Gram positive organisms and Gram negative organisms was found to be (58.97%), and (30.76%), which was similar to Gohel K et al 17 (58.3%) and (40.2%) respectively. The remaining (10.25%) were fungal species.…”
Section: Discussionsupporting
confidence: 89%